Temporal variability of seasonal and annual rainfall in Nepal - Bagale, Damdar (Journal of Nepal Hydrogeological Association, 2024)
This study analyzed 107 weather stations' 42-year rainfall data (1977-2018), using the normal ratio method to estimate missing rainfall from nearby stations. This study identified the mean winter, monsoon, and annual rainfall as 69.7 mm, 1433.2 mm, and 1791.5 mm respectively. The winter, monsoon, and annual rainfall have large temporal variability. Nepal received high rainfall from Jun to September (monsoon) and the rest of the eight months received low rainfall causing water scarcity in Nepal. This study examined the increase of rainfall with heights up to mid-mountain then the rainfall decreases with height in monsoon season. But in winter generally, the rainfall amount increases with height. However, rainfall totals both seasonal and annual have been decreasing since 2000 both nationally and regional-wise.